Effects of lateral bone augmentation procedures on peri‐implant health or disease: A systematic review and meta‐analysis. Issue Volume 29:Issue S15(2018) (2nd March 2018) - Sanz‐Sánchez, Ignacio; Carrillo de Albornoz, Ana; Figuero, Elena; Schwarz, Frank; Jung, Ronald; Sanz, Mariano; Thoma, Daniel
Abstract: Objectives: This systematic review evaluated the evidence on the effect of the interventions aimed for lateral ridge augmentation (both simultaneously with implant placement or as a staged procedure) on peri‐implant health or disease. Methods: A protocol was developed to answer the following PICO question: "In patients with horizontal alveolar ridge deficiencies (population), what is the effect of lateral bone augmentation procedures (intervention and comparison) on peri‐implant health (outcome)?" Included studies were randomised controlled trials or controlled clinical trials with a follow‐up of at least 12 months after implant loading. Meta‐analyses were performed whenever possible, including subgroup analysis based on follow‐up. Results: Twelve final publications from eight investigations were included. The results from the meta‐analysis indicated that irrespective of the type of intervention, the inflammatory changes, based on bleeding on probing (%) were minimal, both at short‐ ( n  = 1; weighted mean difference [WMD] = −1.00; 95% CI [−14.04; 12.04]; p  = .881) and long‐term ( n  = 5; WMD = −5.63; 95% CI [−18.42; 7.16]; p  = .881). When comparing different treatment modalities, no significant differences were observed ( n  = 6; WMD = −3.36; 95% CI [−12.49; 5.77]; p  < .471). Similarly, changes in probing pocket depth and marginal bone levels were not significantly different among groups. The incidence of peri‐implantitis was evaluated in three investigations and varied from 16% to 26% after a follow‐up period of 6–8 years. Conclusions: The results from this systematic review and meta‐analysis have shown that lateral ridge augmentation procedures can maintain peri‐implant health over time with low mucosal inflammatory changes and a relatively small incidence of peri‐implant bone loss.